ANALISIS PEMAHAMAN MATEMATIS MAHASISWA DALAM MENYELESAIKAN SOAL ANALISIS REAL 1 DITINJAU DARI COGNITIVE STYLE FIELD DEPENDENT DAN FIELD INDEPENDENT - Jurniyati; Takdir; Fitriani (MEGA: Jurnal Pendidikan Matematika, 2021)
Analysis of Students' Mathematical Understanding in Solving Real 1 Analysis Question Viewed from the Cognitive Style Field Dependent and Field Independent of Mathematic Education Study Program IAI Muhammadiyah Sinjai. Thesis. Sinjai: Mathematic Education Study Program. Faculty of Tarbiyah and Teacher Training IAI Muhammadiyah Sinjai, 2021. This study aims to describe: (1) students' mathematical understanding in solving real 1 analysis questions in terms of cognitive style field dependent; (2) students' mathematical understanding in solving real 1 analysis questions in terms of cognitive style field independent. This research is a case study research using a qualitative approach. The subjects of this study were students of fourth semester of the Mathematic Education Study Program. The method of data collection is by interview and solve question test. While the data analysis is done through data reduction, data presentation and drawing conclusions. The results of this study indicate that students' mathematical understanding in solving real 1 analysis questions in terms of cognitive style field dependent, namely students understand the problem by reading the problem, making an understood plan of completion and then completing the solution plan based on the understanding of previous learning, then checking the answers by rereading the question. Thus, students do not understand mathematically the test of solving real 1 analysis question given. Meanwhile, students' mathematical understanding in solving real 1 analysis questions in terms of cognitive style field independent, namely students understand the problem by reading the questions, making a solution plan that is understood and considered appropriate and then completes the plan based on the steps that have been made and understanding in previous learning then checks the answers by testing the solution steps. Thus, students do not understand mathematically the test of solving real 1 analysis question given even though students have completed the test and can explain the steps for solving it.